Analysis of Employee Performance with The Role of Organizational Commitment as A Moderation Variable In Amusement Park Tourism Companies in The City of Surabaya - Muhammad Taufiqurrahman; Tri Kartika Pertiwi; Dhani Ichsanuddin Nur (Return : Study of Management, Economic and Bussines, 2023)
The research aims to understand the impact of work discipline and competence in part on the performance of employees as well as the influence of working disciplines and competences on Employee Performance with organizational commitment as a variable of moderation. This case study was conducted on one of the tourism companies that moved in the area of amusement parks in the city of Surabaya. The sample in this study consisted of 103 permanent employees with saturated/sensus sampling techniques. The type of data used is quantitative data. Primary data collection techniques use questionnaires distributed to permanent employees and secondary data of permanent employees from the entertainment park tourism company in the city of Surabaya. This study uses Smart PLS data analysis. The conclusions of this study showed that in part work discipline and competence contributed to improved Employee Performance, while organizational commitment as moderation could not contribute to the relationship of work disciplines and competencies in improving Employee Performances.